Records of the Society for Establishing Useful Manufactures - Society for Establishing Useful Manufactures
Correspondence relating to stock transactions and printed shares of stock for the Society for Establishing Useful Manufactures. Persons represented include Elisha Boudinot, Peter Van Brugh Livingston, James Picketts, and William Seton, and the firm of Armstrong & Barnewall.
First business corporation formed in New Jersey. Established by Alexander Hamilton and others in 1791. Manufacturers of textiles. Suspended operations briefly in 1796, but continued in various endeavors into the twentieth century. Mills at Paterson, N.J., and other locations.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Boudinot, Elisha, -- 1749-1819.; Hamilton, Alexander, -- 1757-1804.; Livingston, Peter Van Brugh, -- 1710-1792.; Picketts, James; Seton, William, -- 1746-1798.; Armstrong & Barnewall (Firm); Stocks; New Jersey -- Commerce -- History; Paterson (N.J.) -- Commerce